Fortification of Milkfish Bone Flour (Chanos chanos) and Seaweed Flour (Sargassum sp.) on Tortilla Chips as a Calcium Foods - Probowati, Fiona Bayun; Alamsjah, Mochammad Amin; Pujiastuti, Dwi Yuli (Indonesian Journal of Agricultural Research, 2024)
Tortilla chips are one of the typical snacks that come from Mexico, and have a shape like chips made from corn. The level of public awareness of the need for milk consumption is indeed very low. Alternative foods with calcium are snacks by fortification. Calcium intake in the recommended range is between 800-1200 mg per day. This study aims to determine the combination of milkfish bone flour and Sargassum sp. with different concentrations of tortilla chips as a calcium food. This study was experimental using a completely randomized design (CRD) with four treatments and five replications. The treatment in this study was the concentration variation of the combination of milkfish bone flour and Sargassum sp. seaweed. (0%, 5%, 10%, 15%). Analysis of the organoleptic test data used the Kruskal-Wallis test and the Mann-Whitney advanced test while the chemical test used the ANOVA test and Duncan's advanced test. The results showed that there was a significant influence (P<0.05) on the best results of the organoleptic test and calcium test on tortilla chip products.